2023
DOI: 10.1002/biof.1940
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of N‐(2‐Hydroxyethyl)hexadecanamide from Colletotrichum gloeosporioides with apoptosis‐inducing potential in breast cancer cells

Abstract: Endophytic fungi are a well-established reservoir of bioactive compounds that are pharmaceutically valuable and therefore, contribute significantly to the biomedical field. The present study aims to identify the bioactive anticancer compound from ethyl acetate extract of fungal endophyte, Colletotrichum gloeosporioides associated with the leaf of the medicinal plant Oroxylum indicum. The fatty acid amide compound N-(2-Hydroxyethyl)hexadecanamide (Palmitoylethanolamide; PEA) was identified using antioxidant act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 82 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…Similar to a previous report, our findings suggest that Kpot·H 2 O and its complexes possess the ability to target reactive oxygen species (ROS) in the proximity of DNA, thereby protecting DNA from harmful radical-induced damage. 58…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to a previous report, our findings suggest that Kpot·H 2 O and its complexes possess the ability to target reactive oxygen species (ROS) in the proximity of DNA, thereby protecting DNA from harmful radical-induced damage. 58…”
Section: Resultsmentioning
confidence: 99%
“…Similar to a previous report, our findings suggest that Kpot•H 2 O and its complexes possess the ability to target reactive oxygen species (ROS) in the proximity of DNA, thereby protecting DNA from harmful radical-induced damage. 58 Kpot•H 2 O and its complexes 1 and 2 exhibit cytotoxic activity. The MTT assay is commonly used to assess the viability, proliferation, and cytotoxicity of a chemical compound so that it can be evaluated for its potential as a drug.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…54 According to several studies, the MDA-MB-231 and MCF-7 cells induced apoptosis and displayed the typical morphological changes associated with apoptosis, including cell shrinkage, nuclei blebbing, chromatin condensation, and nuclear fragmentation. [55][56][57][58] Furthermore, the increased expression of genes associated with apoptosis and the stimulation of the pro-apoptotic protein Caspase-3 evidence that the EA extract of P. oxalicum facilitates apoptosis in breast cancer cells. This suggests that the bioactive compound present in the EA extract of P. oxalicum has potential to induce apoptosis, a crucial mechanism for suppressing the growth of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that PEA docked to the active site of apoptosis-inducing proteins Bax, Bcl-2, P21, and P53, and in vitro findings suggest the cytotoxic and apoptosis-inducing ability of PEA against human breast cancer cells . PEA exhibited enhanced pro-apoptotic activity in human breast cancer cells, MDA-MB-231 and MCF-7, through the modulation of gene expression associated with the intrinsic ( BAX , BCL-2 , P21 , and P53 ) and extrinsic ( CASPASE-8 and FADD ) apoptotic pathways . To the best of our knowledge, the preclinical therapeutic potential of PEA in the amelioration of DMBA-induced breast cancer progression is limited.…”
mentioning
confidence: 97%
“…PEA, an endocannabinoid-like lipid mediator, is recognized for its anti-inflammatory and neuroprotective properties . A recent study reported that PEA docked to the active site of apoptosis-inducing proteins Bax, Bcl-2, P21, and P53, and in vitro findings suggest the cytotoxic and apoptosis-inducing ability of PEA against human breast cancer cells . PEA exhibited enhanced pro-apoptotic activity in human breast cancer cells, MDA-MB-231 and MCF-7, through the modulation of gene expression associated with the intrinsic ( BAX , BCL-2 , P21 , and P53 ) and extrinsic ( CASPASE-8 and FADD ) apoptotic pathways .…”
mentioning
confidence: 99%